2014
DOI: 10.1007/s13277-014-2400-4
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of multidrug resistance gene 1 (MDR1) and risk of chronic myeloid leukemia

Abstract: Multidrug resistance gene 1 (MDR1) is known for its involvement in the detoxification through the active transport of toxic compounds from diverse origins outside the cells. These compounds could cause injury to cell DNA, which might lead in cancer like chronic myeloid leukemia (CML). Individual inherited genetic differences related to polymorphism in detoxification enzymes could be an important factor not only in carcinogen metabolism but also in susceptibility of cancer. The present study aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…while the heterozygous 3435CT in Exon 26 seemed to have a 169 protective effect [19]. These significant findings were not found in 170 our study.…”
Section: Mdr1contrasting
confidence: 57%
See 2 more Smart Citations
“…while the heterozygous 3435CT in Exon 26 seemed to have a 169 protective effect [19]. These significant findings were not found in 170 our study.…”
Section: Mdr1contrasting
confidence: 57%
“…2677GT genotype seemed to have a protective effect in CML 164 (OR = 0.6; 95% CI: 0.32-1.1, P = 0.074) [19]. Genetic background 165 and the tumor originations may play an important role for the 166 different associations.…”
Section: Mdr1mentioning
confidence: 96%
See 1 more Smart Citation
“…P-gp is encoded by the human multidrug resistance-1 gene (MDR1), located on chromosomal region 7q21.1 [6]. Some single nucleotide polymorphism (SNP) studies in MDR1 gene have indicated their effect on gene expression and/or protein function, which might be associated with development of cancers, chemotherapy response, and clinical prognosis in tumor patients [8][9][10]. Among the discovered SNPs, C1236T (Exon 12, rs1128503), C3435T (Exon 26, rs1045642), and G2677T/A (Exon 21, rs2032582) are the most common and mainly focused on polymorphisms in the coding region of MDR1 [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping of C1236T and C3435T SNPs was done by polymerase chain reaction, restrictive fragment length polymorphism. The primer sequences, enzymatic restriction conditions, and digestion product sizes were previously described [ 26 , 27 ]. To identify the genotypes of GSTM1 and GSTT1 , a multiplex polymerase chain reaction (PCR) was performed, in which BCL2 gene was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%